Quantifying environmental performance of biomass energy - Joselin Herbert, G.M.; Unni Krishnan, A. (Renewable & sustainable energy reviews, 2016)
The world needs an enormous amount of energy to maintain the future economic developments. India has facile ways to overcome the immediate demand on energy supply by renewable energy resources. It has a huge potential of biomass resources to reduce the dependence on fossil fuels and to produce electrical and heat energy. The biomass energy can contributes to social and economic development. It has been identified as an alternative for the future energy demand in India. As part of furthering the development of biomass technology, it is essential to understand the environmental merits and demerits of biomass. It also aims to increase the use of biomass energy for domestic purposes. The interest behind the review is boosted by the rapid development of biomass conversion techniques and continual increase of biomass energy generation. It has motivated the authors to collect the quintessential literature of environmental aspects of biomass energy. The objective of the research work is to quantify and focuses the environmental performance of biomass energy. It also deals with the environment monitoring and control, pricing, standard and regulations of the bio-energy for the future development.